2022
DOI: 10.3389/fpubh.2022.901480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia and Its Associated Factors Among Japanese Preschool Children

Abstract: PurposeTo investigate the prevalence of myopia and factors associated with spherical equivalent (SE), axial length (AL), and axial length to corneal radius of curvature (AL/CR) ratio among Japanese preschool children.Study DesignProspective observational study.MethodsThis cross-sectional study evaluated subjects aged 4–6 years from a preschool. Non-cycloplegic autorefraction was measured using the Spot Vision Screener, while AL and corneal radius (CR) were measured using the Myopia Master. Parental myopia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
2
12
0
2
Order By: Relevance
“…They demonstrated that the AL/CRC ratio was the most important biometric factor in myopia. Some researchers further confirmed Grosvenor’s findings 29 43 44. The distribution of AL/CRC ratio has been reported in different countries and age populations.…”
Section: Discussionsupporting
confidence: 56%
“…They demonstrated that the AL/CRC ratio was the most important biometric factor in myopia. Some researchers further confirmed Grosvenor’s findings 29 43 44. The distribution of AL/CRC ratio has been reported in different countries and age populations.…”
Section: Discussionsupporting
confidence: 56%
“…The results show that participants that were diagnosed before the age of 10 had higher myopia during the period of studies, reinforcing the statement about the necessity of early diagnosis. Many authors agree that the identification of early myopia cases is a matter of great importance, as it helps with the early application of the countermeasures, including the correction of vision defects [ 18 , 47 , 48 ]. Screening of myopia in children, reinforced with analysis of the family history of myopia in cases at risk of developing high myopia, is proposed as one of the solutions [ 18 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that place of residence in early childhood has no impact on the frequency and magnitude of myopia in this population. Results of different studies show conflicting results regarding the association between myopia and place of residence in childhood [ 47 , 49 , 50 , 51 ]. In a study conducted on 338 freshman students in Saudi Arabia (162 males, 176 females), place of residence had no effect on myopia progress [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] The following de nitions and classi cations were employed: (1) Myopia was de ned as non-cycloplegic SE ≤ -0.50 D + UCVA > 0.3 log MAR (age 3), > 0.2 log MAR (ages 4-5), > 0 log MAR (age ≥ 6). [14,15] (2) Myopia was categorized into low myopia (-3.00 D < SE ≤ -0.50 D), moderate myopia (-6.00 D < SE ≤ -3.00 D), and high myopia (SE ≤ -6.00 D).…”
Section: Assessment Criteriamentioning
confidence: 99%